A French nationwide study compared various conditions and healthcare use of individuals < 65 years with a Down’s syndrome to those without - Tuppin, Philippe; Barthelemy, Pauline; Debeugny, Gonzague; Rachas, Antoine (Scientific reports, 2023)
Few regular national clinical data are available for individuals with Down’s syndrome (IDS) bearing in mind that they are subject to countries variations in medical termination of pregnancy and screening. Individuals < 65 in 2019 were selected in view of the low number of older IDS. Thus, 98% of 52.4 million people with correct data were included from the national health data system. IDS (35,342) were identified on the basis of the International Classification of Diseases 10th revision code (Q90). Risk ratios (RR) were calculated to compare the frequencies in 2019 between IDS and individual without Down’s syndrome (IWDS) of use of health care. The prevalence of IDS was 0.07% (48% women), comorbidities were more frequent, especially in younger patients (24% < 1 year had another comorbidity, RR = 20), as was the percentage of deaths (4.6%, RR = 10). Overall, tumours were less frequent in IDS compared with IWDS (1.2%, RR = 0.7) except for certain leukaemias and testicular tumours (0.3%, RR = 4). Cardiac malformations (5.2%, RR = 52), dementia (1.2%, RR = 29), mental retardation (5%, RR = 21) and epilepsy (4%, RR = 9) were also more frequent in IDS. The most frequent hospital diagnoses for IDS were: aspiration pneumonia (0.7%, RR = 89), respiratory failure (0.4%, RR = 17), sleep apnoea (1.1%, RR = 8), cryptorchidism (0.3%, RR = 5.9), protein-energy malnutrition (0.1%, RR = 7), type 1 diabetes (0.2%, RR = 2.8) and hypothyroidism (0.1%, RR = 72). IDS were more likely to use emergency services (9%, RR = 2.4), short hospital stay (24%, RR = 1.6) or hospitalisation at home (0.6%, RR = 6). They consulted certain specialists two to three times more frequently than IWDS, for example cardiologists (17%, RR = 2.6). This study is the first detailed national study comparing IDS and non-IDS by age group. These results could help to optimize prenatal healthcare, medical and social support.